Неопубликованный боспорский рельеф с изображением всадника [Natalia Pavlichenko. An Unpublished Bosporan Relief of a Horseman] - Павличенко, Н. А. (Hyperboreus, 2011)
The paper presents a fragmentary stele bearing a relief of a horseman galloping left and an inscription Μακάρι[ος υἱός] vel Μακάρι[ε υἱέ] Ἀπο[λ]λων[ίου χαῖρε], whose right and left parts are missing, from the excavations of the Bosporan city of Nymphaeum in 1981. The script of the inscription allows dating the monument to the 1st century A. D. or to the beginning of the 2nd century A. D.